Mechanical Bowel Preparation versus No Preparation in Duhamel Procedure in Children with Hirschsprung's Disease - Hosseinpour, Mehrdad; Ahmadi, Bahareh; Etezazian, Sanaz (European Journal of Pediatric Surgery, 2020)
Introduction Mechanical bowel prep (MBP) prior to surgical treatment of Hirschsprung's disease (HSCR) has been a great problem of pediatric surgeons for a long time. We conducted a single-institution randomized controlled trial to evaluate the efficacy of no MBP in children with HSCR undergoing the Duhamel procedure.Materials and Methods In this study, children with HSCR who were candidate for the Duhamel procedure were included (40 cases vs. 40 controls). In the case group, intraoperatively after transection of the bowel at the level of transitional zone, feces bulk was pulled up from the upper part of the rectum to the sigmoid colon above the peritoneal reflection and aganglionic bowel was resected. Inspissated stool in the distal of the rectum was removed by rectal washout intraoperatively. In the control group, routine MBP was performed. Cleanness of the rectum was evaluated intraoperatively.Results In this study, a total of 80 children were enrolled. In 32 patients (80%), the goal of MPB was achieved in 4 hours. Mean polyethylene glycol volume was 1372.3 ± 231.9 mL. Preoperative rectal washout fluid was 635 ± 233.3 mL. There was no statistically significant difference in individual complication rates between groups. Four patients (5%) had intra-abdominal infection and 16 (20%) had wound infection. We had no anastomotic leak in our groups. All children or parents in the control group described the preoperative MBP as the most unpleasant part of the hospital administration.Conclusion For young children with HSCR who were scheduled for Duhamel operation, we had found no clear benefit of MBP. However, a multicenter randomized controlled trial is needed to more definitely determine the best preoperative approach for children with HSCR.
Keywords: mechanical bowel prep; Hirschsprung's disease; postoperative complications